Medical findings and predictors of long-term physical outcome in anorexia nervosa: a prospective, 12-year follow-up study - Herzog, Wolfgang; Deter, Hans-Christian; Fiehn, Walter; Petzold, Ernst (Psychological medicine, 1997)
Background. Patients with anorexia nervosa (AN) run a high risk of becoming chronically ill and of dying. In the acute phase of their illness they present with numerous physical and laboratory abnormalities. However, little is known about the long-term prognostic value of these findings or about the medical morbidity in large samples of consecutively treated patients in the long-term.Methods. We evaluated 84 consecutive female patients with AN who were studied again an average of 11·9 years later. The ability of some of the laboratory data obtained at the initial examination to predict a fatal or chronic course was analysed by discriminant and multiple regression analyses.Results. Abnormally low serum albumin levels ([les ] 36 g/l) and a low weight ([les ] 60% of average body weight) at the initial examination were variables best able to predict a lethal course. In addition, high serum creatinine and uric acid levels predicted a chronic course. Most of the initial abnormal laboratory findings were reversible with a normal food intake. At a 12-year follow-up 67% of the chronic anorexic patients and 27% of those in the good/intermediate outcome group (compared to 8% morbidity in normal controls) presented with medical co-morbidity, in particular osteoporosis and renal disease. The standardized mortality ratio was 9·6.Conclusions. Laboratory findings obtained at the initial examination may be helpful in predicting a fatal or chronic course of AN. An evaluation of the long-term outcome of eating disorders should include an assessment of the medical co-morbidity.